Problematika Perdagangan Manusia Sebagai Kejahatan Transnasional Dalam Perspektif Imigrasi Dan Hukum Internasional - Rizqi Mei Vindraputri (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Globalization on an international scale has an impact on progress in the fields of information technology, communication and transportation, making borders between countries thinner or borderless. This is a principle in the international legal order, especially regarding the conception of state sovereignty. Every country in various parts of the world is guaranteed in international law and has the exclusive right to exercise its country's sovereignty without being able to intervene by other countries or any party. The sovereignty of a country is an absolute thing that cannot be ignored, because sovereignty is a sign of an independent and sovereign country. International migration that occurs has a positive impact, but sometimes it creates new problems. Like Human Trafficking or human trafficking. The writing will discuss human trafficking from the perspective of immigration and international law, including the function of immigration as a government agency that monitors the traffic of people in and out of Indonesian territory in order to maintain state sovereignty. This research itself is based on research that is normative, juridical and empirical, namely by elaborating each material followed by studying existing policies and regulations. This is intended so that the problem of human trafficking can be elaborated on existing national and international legal policies as well as from an immigration perspective. .